An Efficient Trifunctional Spinel-Based Electrode for Oxygen Reduction/Evolution Reactions and Nonoxidative Ethane Dehydrogenation on Protonic Ceramic Electrochemical Cells - Xu, Yangsen (Advanced materials (Deerfield Beach, Fla.), 2024)
© 2024 Wiley‐VCH GmbH.